China from empire to nation-state - Wang, Hui, 1959- (Harvard University Press, 2014)
[Description]This translation of the introduction to Wang Hui's Rise of Modern Chinese Thought (2004) makes part of his four-volume masterwork available to English readers for the first time. A leading public intellectual in China, Wang charts the historical currents that have shaped Chinese modernity from the Song Dynasty to the present day.